2021
DOI: 10.1051/e3sconf/202131211011
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of GT exhaust gas temperature by acoustic pyrometry: Preliminary error investigation

Abstract: Acoustic pyrometry is an interesting technique that may find several useful applications in turbomachinery. It is well known that the speed of sound in a medium is directly related to its temperature. Acoustic pyrometry estimates the temperature of a gas by considering the time of flight of an acoustic wave moving through it. If one acoustic emitter-receiver couple is used, only the average temperature along the acoustic path can be determined. If multiple emitter-receiver couples laying on the same plane are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…An example of the used computational domain is showed in Fig. In comparison to the temperature estimation by acoustic pyrometry methods [8,9], the reconstruction significantly depends on the angle between the acoustic path and the flow velocity direction angle, and hence requires a more complex approach. Moreover, particular attention should be paid to the path with 𝛼 𝑗 close to 90Β°, for which the terms π‘π‘œπ‘ (𝛼 𝑗 ) tend to zero.…”
Section: Figure 3 Velocity Profile Used As Case Studymentioning
confidence: 99%
“…An example of the used computational domain is showed in Fig. In comparison to the temperature estimation by acoustic pyrometry methods [8,9], the reconstruction significantly depends on the angle between the acoustic path and the flow velocity direction angle, and hence requires a more complex approach. Moreover, particular attention should be paid to the path with 𝛼 𝑗 close to 90Β°, for which the terms π‘π‘œπ‘ (𝛼 𝑗 ) tend to zero.…”
Section: Figure 3 Velocity Profile Used As Case Studymentioning
confidence: 99%
“…The results suggested how both the size of the devices used in the computational procedure and the emitter-receiver couple (ERC) number significantly affect the estimation accuracy and the computational burden. The reliability of the acoustic pyrometry with respect to the number of ERCs used and TOF uncertainty was further investigated by Ferrari et al [9][10][11] through a statistical approach. As a general result, they found that if the TOF estimation is not affected by uncertainty, the estimation accuracy may be improved simply by increasing the number of ERCs.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there have been developments in reconstruction algorithms and the capabilities of electronic processing systems, allowing for reduced reconstruction times and increased spatial and temporal resolution of the method. Recently, several studies investigated the feasibility of using acoustic pyrometry in turbomachinery applications, as reported in [17]- [20]. In a previous study the authors investigated the potential of velocity estimation in a simplified arrangement [21].…”
Section: Introductionmentioning
confidence: 99%